2014
DOI: 10.1186/1471-2474-15-51
|View full text |Cite
|
Sign up to set email alerts
|

The association between lean mass and bone mineral content in the high disease activity group of adult patients with juvenile idiopathic arthritis

Abstract: BackgroundThe study is aimed to evaluate body composition and bone status in adolescent and adult patients with active juvenile idiopathic arthritis (JIA) untreated with tumor necrosis factor alpha inhibitors.MethodsAdult patients (12 male and 19 female) with active JIA and 84 healthy age- and gender- matched controls were enrolled into the study. Body composition (tissue mass in grams, lean mass, fat mass and bone mineral content as a fraction of tissue mass) and areal bone mineral density parameters (aBMD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Juvenile idiopathic arthritis (JIA) is a systemic autoimmune inflammatory connective tissue disease with onset occurring before age 16 years. It is associated with a decrease in bone mass, thinning of the cortical bone [ 1 , 2 ], sarcopenia [ 3 , 4 ] and an increased risk of fractures [ 5 ]. Bone loss may be systemic or localized to the periarticular bone due to arthritis of the affected joint.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile idiopathic arthritis (JIA) is a systemic autoimmune inflammatory connective tissue disease with onset occurring before age 16 years. It is associated with a decrease in bone mass, thinning of the cortical bone [ 1 , 2 ], sarcopenia [ 3 , 4 ] and an increased risk of fractures [ 5 ]. Bone loss may be systemic or localized to the periarticular bone due to arthritis of the affected joint.…”
Section: Introductionmentioning
confidence: 99%
“…While one of the studies showed lower skeletal muscle mass in (female) patients than in controls ( 14), no differences in body fat between patients and controls were found (5,14). For comparison, studies in juvenile onset SLE and JIA have demonstrated lower muscle mass and higher BF% in patients with both early (17,29) and longstanding disease (16,30).…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be explained by the inactive lifestyle of JIA patients [23] due to chronic joint pain [8,24]. The lack of physical activity leads to increased muscle weakness and atrophy that aggravate the altered body composition in JIA patients, where fat mass is increased and bone and lean mass decreased [25,26]. In addition, medications such as glucocorticoids have direct actions on muscle loss and osteoporosis [26].…”
Section: Physical Capacity Of Jia Patientsmentioning
confidence: 95%